2005
DOI: 10.1638/03-126
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoids in Captive Zebras (Equus Burchellii): Association With Bovine Papillomavirus Type 1 Infection

Abstract: Sarcoids were diagnosed in two captive zebras from different facilities. Zebra 1 (Equus burchellii boehmi) was a 4.5-yr-old, captive-born male that presented with a 9- by 7-cm inguinal mass. Seven months after surgical excision of the inguinal mass, the zebra presented with a similar lesion in the right upper eyelid that has relapsed repeatedly and has not responded to treatment including local cisplatin injections and cryosurgery. Zebra 2 (of undetermined taxon) was housed at a private wild animal farm. The z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 16 publications
2
26
0
2
Order By: Relevance
“…BPV DNA has not been detected in other equine tumors, including melanomas, papillomas, and squamous cell carcinomas (15), although we and others have shown that BPV-1/BPV-2 DNA can be detected in some cases of equine inflammatory skin disease (3,15,68). BPV DNA is localized to the fibroblast nuclei (37,60) and is maintained as a high-copynumber episome, and infection results in the expression of viral genes (2,10,15,49,67). We have recently shown that BPV-1 transforms primary equine fibroblasts (69).…”
mentioning
confidence: 65%
“…BPV DNA has not been detected in other equine tumors, including melanomas, papillomas, and squamous cell carcinomas (15), although we and others have shown that BPV-1/BPV-2 DNA can be detected in some cases of equine inflammatory skin disease (3,15,68). BPV DNA is localized to the fibroblast nuclei (37,60) and is maintained as a high-copynumber episome, and infection results in the expression of viral genes (2,10,15,49,67). We have recently shown that BPV-1 transforms primary equine fibroblasts (69).…”
mentioning
confidence: 65%
“…Comparing levels of average heterozygosity, mean number of alleles per loci, effective number of alleles, mean range of microsatellite repeats and microsatellite variance estimates between a population of interest and its free-ranging counterpart are useful to determine loss of genetic variation. The appearance of sarcoid tumours in equids has been correlated with specific genetic haplotypes (Chambers et al 2003) with the involvement of BPV in the formation of sarcoid tumour in equids proven (Lohr et al 2005;Brandt et al 2008) and correlated with down-regulation of immune system genes (Ashrafi et al 2006;Yuan et al 2008). The only previous epizootic of sarcoid tumour reported was in horses, with four of the five affected individuals being members of a highly inbred herd (Ragland et al 1966).…”
Section: Discussionmentioning
confidence: 99%
“…At a minimum, the skin should be checked for parasites and sarcoids (the most common tumor in zebras), 11 the joints flexed, the hooves inspected, and the oral cavity and mucous membranes visualized. The examination should be efficient without unduly prolonging the anesthesia.…”
Section: Dartingmentioning
confidence: 99%